Penyuluhan Pertolongan Pertama Pada Kecelakaan (P3K) Sekolah Menengah Pertama di Kabupaten Bondowoso - Billy Emir Rizkanto; Riga Mardhika; Eka Kurnia Darisman; Muhammad Wahyono; Yandika Fefrian Rosmi; Shinta Nuriyah Anwar; Putri Juliah Anisah (Kanigara, 2023)
Children are an age that is prone to accidents or injuries, because the are curious about things around them, in school student are starting to enter their teens. Therefore, it is necessary for school resident, especially teachers, to know how to do first aid when accident happens, so the are able to apply and teach student and the local community. The method of implementing activities tha have been carried out is in form of exploratory discussions and practice of handling injuries. Result knowledge about first aid in an accident in the school is needed by all components in the school. Both student through teachers, so that when an injuru occurs, they can perform first aid properly